Intercultural communication in contexts - Martin, Judith N.; Nakayama, Thomas K. (McGraw-Hill, 2013)
Examines communication in multicultural relationships and provides practitioners with the tools for effective communication amid cultural, ethnic, and religious differences. This title introduces students to primary approaches for studying intercultural communication along with a theoretical and practical framework for applying these approaches